Mapping QTLs for Fusarium Head Blight Resistance in an Interspecific Wheat Population - Giancaspro, Angelica; Giove, Stefania L.; Zito, Daniela; Blanco, A.; Gadaleta, Agata (Frontiers in Plant Science, 2016)
Fusarium head blight (scab) is one of the most widespread and damaging diseases of wheat, causing grain yield and quality losses and production of harmful mycotoxins. Development of resistant varieties is hampered by lack of effective resistance sources in the tetraploid wheat primary gene pool. Here we dissected the genetic basis of resistance in a new durum wheat (Triticum turgidum ssp. durum) Recombinant Inbred Lines population obtained by crossing an hexaploid resistant line and a durum susceptible cultivar. A total of 135 Recombinant Inbred Lines (RILs) were used for constituting a genetic linkage map and mapping loci for head blight incidence, severity and disease-related plant morphological traits (plant height, spike compactness, awn length). The new genetic map accounted for 4,366 SNP markers assembled in 52 linkage groups covering a total length of 4,227.37 cM. Major QTL for scab incidence and severity were mapped on chromosomes 2AS, 3AL and 2AS, 2BS, 4BL, respectively. Plant height loci were identified on 3A, 3B and 4B, while major QTL for ear compactness were found on 4A, 5A, 5B, 6A and 7A. In this work resistance to Fusarium was transferred from hexaploid to durum wheat, and correlations between the disease and morphological traits were assessed.